Estresse laboral e suas consequências psicossociais em policiais militares no exercício de suas funções - Alves, Verlene Sousa de Castro (2018)
The police institution is present in several countries and is identified by the use of force and coercion to try to maintain good social functioning. Specifically, the profession of military police is associated with the characteristics of abuse of power and authoritarianism, being considered also a labor activity of potential stress and risk of professionals losing their lives in their work routines. The surveys so far suggest the lack or little psychological follow-up of these professionals after the initial psychological examination for admission into office. With the objective of understanding the impacts of the working context, the relationship they have with some indicators of mental illness, such as: stress, anxiety, depression and suicidal ideation, and ultimately aggression, this study proposed an explanatory model of Aggression from the analyzed variables. For the realization of this research, it was counted with a sample of 229 military police officers. Participants responded to the work context scale (EACT) belonging to the work inventory and risk of illness (ITRA); Stress scale at work (EET); General Health Questionnaire (QSG); Multi-attitudinal range of suicidal tendencies (EMATS); Buss-Perry Aggression questionnaire. The data collection occurred in the police units. It is emphasized that all ethical procedures were adopted in order to make the research viable. The analysis of the data was carried out by IBM SPSS Statistics 22 and Amos 22. The hypotheses tested by simple and multiple linear regression presented similar results to the research literature, in which the work context promotes labor stress and mental illness, as well as the stress and variables related to the mental illness explain the aggression. The results supported the explanatory and integral model in which the working context raises the index of labour stress; Which, in turn, favors the mental illness, influencing increased aggression. Therefore, it is entrusted that the results achieved have enabled us to test the suggested variables and obtain relevant information on these indicators contributing to the field of mental health and public safety.